RELEVANSI KOMPETENSI LULUSAN - Novi Satria Pradja; Ammar Ammar Chania (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
The University had main of task to prepare profesional scholars. The profile ofgraduates is a benchmark for the success of an education institution. This is importance to searchabout trace the development of graduates after finished education as an evaluation of institution.Focus of graduates trace record is the measurement of learning outcome factors with record theprofile of graduates divided into three main focus, namely the study period, graduates career, andgraduates competent. This research uses a study descriptive qualitative with subject as graduates ofthe 2016 and 2017 in Faculty of Teacher Training and Education Kuningan University. The datacollected instruments used questionnaires and interview guideline. Analysis data, research usedtechniques that include data reduction, display, and conclusion or verification.The results of the analysis show that the 2016 and 2017 Faculty of Teacher Training and Educationfrom Kuningan University: 1) the average time need to finished study is 8 semesters, 2) 59% fromthe graduates can relevant work with study and becoming a teacher, and 3) the stakeholdersassessing graduates as has sufficient competence.Keywords: Time of Study Period, Career of Graduates, Competent of Graduates